Peran Guru dan Orang Tua dalam Membangun Karakter Mandiri Autisme Anak Usia Dini RA Miftahul Ulum Probolinggo - Linawati, Linawati; Dirgahayunita, Aries (Lembaga Yasin AlSys, 2025)
This study aims to explore effective learning strategies for fostering independent character development in children with autism through the synergy between teachers and parents at RA Miftahul Ulum in Probolinggo City. Children with autism often face social stigma and discrimination, both from society and their own family environments. Observations conducted at RA Miftahul Ulum reveal that most parents of children with autism encounter significant difficulties in understanding appropriate approaches to educate their children at home. This situation creates a complex dilemma in addressing the special needs and behaviors of children with autism, particularly in efforts to develop their independence. This research employs a descriptive qualitative approach to deeply investigate the roles of teachers and parents in shaping the independent character of children. Data collection techniques utilized purposive sampling to determine participants, while data analysis followed the Miles and Huberman model. The findings indicate that with solid collaboration between teachers and parents, various challenges can be effectively addressed, enabling children with autism not only to reach their optimal potential at school but also to apply their independence in daily life. The learning strategies implemented include an inclusive approach, reinforcement of social skills, life skills education, and emotional support. These collective efforts contribute significantly to the development of independent character in students. This study underscores the critical role of collaboration in overcoming obstacles and ensuring sustainable progress in the education and personal growth of children with autism.